Resonance Spectra of Caged Stringy Black Hole and Its Spectroscopy - I. Sakalli; G. Tokgoz (Advances in High Energy Physics)
Maggiore’s method (MM), which evaluates the transition frequency that appears in the adiabatic invariant from the highly damped quasinormal mode (QNM) frequencies, is used to investigate the entropy/area spectra of the Garfinkle–Horowitz–Strominger black hole (GHSBH). Instead of the ordinary QNMs, we compute the boxed QNMs (BQNMs) that are the characteristic resonance spectra of the confined scalar fields in the GHSBH geometry. For this purpose, we assume that the GHSBH has a confining cavity (mirror) placed in the vicinity of the event horizon. We then show how the complex resonant frequencies of the caged GHSBH are computed using the Bessel differential equation that arises when the scalar perturbations around the event horizon are considered. Although the entropy/area is characterized by the GHSBH parameters, their quantization is shown to be independent of those parameters. However, both spectra are equally spaced.